The Impact of Microfinance on Rural Development in India - Bharuka, Sangita; Mehta Soni, Renu (Journal of Commerce and Trade, 2015)
Microfinance is used toa supply small credits to very poora section of society sthat is unable to access the traditional economicala financial institutions such as banks. It helpAs them in acquiring finance to expand their tinya businesses and other financial needs. Microfianances also helps in improvinga contribution of women in economic activitiesa by providinga economical resources to invest. Thisa research paper is an effort to bring light the role of microfinance in rural development through the study of micro financial schemes. We can learn important lessons from microfinance for developments in terms of what can be the strategy that we can adapt to make a difference. We can conclude that weak sector of Indian economy is in dire need of money lending methods to earn credits so microfinance programs should be an important area of focus to provide these people the chance to improve their standard of living via means of economical growth.